2019
DOI: 10.29333/ejmste/110490
|View full text |Cite
|
Sign up to set email alerts
|

Meaning and Understanding of School Mathematical Concepts by Secondary Students: The Study of Sine and Cosine

Abstract: Meaning and understanding are didactic notions appropriate to work on concept comprehension, curricular design, and knowledge assessment. This document aims to delve into the meaning of school mathematical concepts through their semantic analysis. This analysis is used to identify and establish the basic meaning of a mathematical concept and to value its understanding. To illustrate the study, we have chosen the trigonometric notions of sine and cosine of an angle. The work exemplifies some findings of an expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 26 publications
0
13
0
2
Order By: Relevance
“…Junior secondary students continue with learning Pythagorean theorem and basic trigonometry defined as ratios of sides and using these basic rules to solve problems associated with right triangles [3][4][5]. Senior secondary students progress further with trigonometric identities, functions and relationships, law of sines, law of cosines and law of tangent to solve oblique triangles in scientific and engineering problems [6][7][8][9]. As a result, triangles and their applications have been an important part in mathematics curriculums for pre-service mathematics teachers in tertiary institutions in the world [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Junior secondary students continue with learning Pythagorean theorem and basic trigonometry defined as ratios of sides and using these basic rules to solve problems associated with right triangles [3][4][5]. Senior secondary students progress further with trigonometric identities, functions and relationships, law of sines, law of cosines and law of tangent to solve oblique triangles in scientific and engineering problems [6][7][8][9]. As a result, triangles and their applications have been an important part in mathematics curriculums for pre-service mathematics teachers in tertiary institutions in the world [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Mathematical understanding can be constructed within a suitable semantic framework to describe and interpret its meaning. The research of Martín-Fernández & Ruiz-Hidalgo (2019) shows that 88% of students have expressed their understanding of the concepts of sine and cosine based on the idea of coherent meaning with a good semantic framework.…”
Section: Figure 3 Examples Of Student Workmentioning
confidence: 99%
“…This is in line with the study of Boaler et al (2016) that teaching and learning mathematics needs to explore mathematical concepts more visually. The study of Martín-Fernández & Ruiz-Hidalgo (2019) show that 88% of students have expressed their understanding of the concepts of sine and cosine based on the idea of coherent meaning with a good semantic framework.…”
Section: Figure 3 Examples Of Student Workmentioning
confidence: 99%
“…Many studies [11,12] have reported that students understand sines and cosines in three ways namely (i) as the point-to-circle coordinates, (ii) as a coordinate of horizontal and vertical line, and (iii) as the ratio of the triangle sides. Trigonometric problem solving is strongly influenced by the stages chosen by students [13].…”
Section: Introductionmentioning
confidence: 99%